Temporomandibular disorders during the COVID 19 pandemic - Meneses-Rivadeneira, Leopoldo (2022)
After two years of having identified in Wuhan - China the respiratory infection caused by SARS-CoV-2 that has caused the last global pandemic, we continue to experience the uncertainty of what is known, what is not yet known and observing what that the pandemic is leaving us. Among the many health problems that have been caused by the pandemic, stomatological problems have not only increased due to lack of care, but also some epidemiological data that characterized them have changed. Thus, temporomandibular disorders (TMD) have almost doubled in number in adolescents and young adults, which is associated with the multiple adverse psychological reactions that have generated excessive fear, anxiety and depression due to the COVID-19 pandemic. The purpose of this publication is to present a review of the current context of temporomandibular disorders.